Dynamic High Resolution Hydrological Status Monitoring in Real-Time: The UK Water Resources Portal - Barker, Lucy J.; Fry, Matt; Hannaford, Jamie; Nash, Gemma; Tanguy, Maliko; Swain, Oliver (Frontiers in Environmental Science, 2022)
Understanding the current hydro-meteorological situation is critical to manage extreme events and water resources. The UK Water Resources Portal (UKWRP) has been developed to enable dynamic, interactive, real-time access to hydro-meteorological data across the UK, including catchment daily rainfall, (near) real-time daily mean river flows, groundwater levels and real-time soil moisture data, and standardised climate indices. The UKWRP offers a way of exploring the full range of river flow and rainfall variability, including comparing current conditions to those in the past, from droughts to floods. A variety of different plotting capabilities mean users can view and explore data in different ways depending on their requirements. Here we discuss the mechanisms and the engagement undertaken to develop the UKWRP, in addition to the technical issues and solutions of bringing multiple data sources and types together, how the data are processed, stored and published to deliver an integrated tool for water resources management. The UKWRP enables all water users – from farmers, to water companies to members of the general public – to view and explore the data used by regulators to manage water supplies. We demonstrate how the UKWRP can be used to monitor the hydrological situation, using recent examples of both floods and droughts, and enables consistent messaging and universal access to data and information. Finally, we discuss the decisions the information provided in the UKWRP can support, and possible future developments. The UKWRP is aimed at the UK water research and management community, but we envisage that the Portal (and the development pathway and technical solutions reported here) could provide a useful exemplar for similar systems in other international settings.